2021
DOI: 10.1249/mss.0000000000002624
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training’s Ability to Prevent Cancer-induced Muscle Atrophy Extends Anabolic Stimulus

Abstract: Purpose: This study aimed to determine the role of mammalian target of rapamycin (mTORC1) activation and catabolic markers in resistance training's (RT) antiatrophy effect during cachexia-induced muscle loss. Methods: Myofiber atrophy was induced by injecting Walker 256 tumor cells into rats exposed or not exposed to the RT protocol of ladder climbing. The role of RT-induced anabolic stimulation was investigated in tumor-bearing rats with the mTORC1 inhibitor rapamycin, and cross-sectional areas of skeletal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…STAT3-phosphorylated protein content was markedly elevated in the skeletal muscle of tumor-bearing mice compared to the controls (Figure 4A). In agreement with previous studies using different cancer cachexia models (5,6,18), Ehrlich tumor development presented characteristics of pro-inflammatory scenario, as demonstrated by significant (P <.05) elevated TNFa and IL-6 in plasma of tumor-bearing mice compared to the control group (Figures 4B, C). Tumor-bearing mice also presented skeletal muscle oxidative damage, as demonstrated by elevated levels (P <.05) of the lipid peroxidation evaluated by TBARS, protein oxidation evaluated by AOPP, and redox imbalance demonstrated by elevated skeletal muscle GSSG concentration and reduced GSH/GSSG ratio (Figures 4D-F).…”
Section: Rt Attenuated Muscle Atrophy By Preventing Stat3 Phosphoryla...supporting
confidence: 92%
See 2 more Smart Citations
“…STAT3-phosphorylated protein content was markedly elevated in the skeletal muscle of tumor-bearing mice compared to the controls (Figure 4A). In agreement with previous studies using different cancer cachexia models (5,6,18), Ehrlich tumor development presented characteristics of pro-inflammatory scenario, as demonstrated by significant (P <.05) elevated TNFa and IL-6 in plasma of tumor-bearing mice compared to the control group (Figures 4B, C). Tumor-bearing mice also presented skeletal muscle oxidative damage, as demonstrated by elevated levels (P <.05) of the lipid peroxidation evaluated by TBARS, protein oxidation evaluated by AOPP, and redox imbalance demonstrated by elevated skeletal muscle GSSG concentration and reduced GSH/GSSG ratio (Figures 4D-F).…”
Section: Rt Attenuated Muscle Atrophy By Preventing Stat3 Phosphoryla...supporting
confidence: 92%
“…RT was performed as previously described in a ladder-climbing protocol for rats (5,6,19) adapted to mice. RT consisted of a set of ladder-climbing (0.5m, 0.01m grid, 900 incline) projected so it favored 8-12 dynamic movements per climb.…”
Section: Rt Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous ( Jee et al, 2016a ) and current studies also showed the cancer-suppressive effect of high-intensity aerobic exercise. Other studies demonstrated that resistant exercise on the animal cancer model mitigates tumor growth, tumor grade, viable tumor area, tumor cell proliferation, and myofiber atrophy-causing cancer cachexia via attenuating some key markers such as TNF-α, IL-6, Atrogin1, and oxidative damage ( Padilha et al, 2019 ; Padilha et al, 2021 ). In addition, we also found an effect of exercise on cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent microarray-based study on the effect of low-intensity resistance training on human subjects showed that the accurate mode and extent of exercise resulted in the upregulation of microRNAs, such as miR-630 and miR-5703, and myokines (fractalkine/CX3CL1) among 42 pathways and 12 cytokines/myokines, which subsequently suppressed tumor growth by inducing tumor-specific cytotoxic T cells ( Hashida et al, 2021 ). In addition, the ladder climbing resistant training exercise on preclinical tumor-bearing animals also mitigated muscle atrophy, tumor growth, and cancer malignancy ( Padilha et al, 2019 ; Padilha et al, 2021 ). However, the molecular mechanisms underlying the anticancer effects of exercise remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%